Impact of competition and voucher school subsidy law on education quality in Chile (2021)
We analyzed the effect of competition and the Preferential School Subsidies (SEP) Law on the quality of Chilean schools for the period 2000-2013. We use dynamic panel regressions, and we show that competition has a positive and non-linear effect on education quality. The initial positive effect of competition on education quality is not persistent and is reversed for high levels of competition. The impact of competition on education quality also depends on the administrative dependence of schools. The SEP Law increased education quality, but through competition the inequality between public and private schools deepened. These results are relevant for the design of public policies aimed at reducing inequality in Chilean education.